2013
DOI: 10.5114/wo.2013.35281
|View full text |Cite
|
Sign up to set email alerts
|

Prealbumin is a more sensitive marker than albumin to assess the nutritional status in patients undergoing radiotherapy for head and neck cancer

Abstract: Aim of the studyThe aim of this prospective study was to determine the prevalence of malnutrition and to evaluate a more sensitive marker to assess the nutritional status in patients undergoing RT for head and neck cancer.Material and methodsThe prospective study included 51 (mean age of 57.6 ±11.2 years) patients undergoing RT for head and neck cancer. Malnutrition was defined as weight loss > 5% of baseline.ResultsForty-six (90.2%) of 51 patients were male. Malnutrition developed in 33 (64.7%) patients durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 14 publications
2
52
0
Order By: Relevance
“…On the other hand, the albumin level did not differ significantly between the two groups. 42,43 In immunocompetent patients, a total lymphocyte count lower than the range 1200-1500 mm -3 was recognised as another indicator of malnutrition. 40 …”
Section: Nutritional Screening and Assessmentmentioning
confidence: 99%
“…On the other hand, the albumin level did not differ significantly between the two groups. 42,43 In immunocompetent patients, a total lymphocyte count lower than the range 1200-1500 mm -3 was recognised as another indicator of malnutrition. 40 …”
Section: Nutritional Screening and Assessmentmentioning
confidence: 99%
“…Previous studies showed that prealbumin has a shorter half-life of 2-3 days and its amount in the body is low. 21 Therefore, measurement of prealbumin is a good marker of visceral protein status and prealbumin is affected earlier by acute variations in protein balance. 37,38 Serum albumin is commonly used as a surrogate marker of nutrition; however, its half-life of 21 days and its steady state level of 100 days limit its utility and value.…”
Section: © 2020 Tottori University Medical Pressmentioning
confidence: 99%
“…37 Therefore, prealbumin is considered superior to albumin in nutritional assessment. 21 Furthermore, prealbumin has recently been identified as an independent prognostic factor in various cancers. 39,40 Based on this theoretical advantage, CRP/PAlb may be more sensitive and superior to CRP/Alb for tumor prognosis.…”
Section: © 2020 Tottori University Medical Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu found that C-Reactive protein/Albumin (CRP/ ALB) was superior to traditional inflammatory indices in predicting long-term survival of GC [6]. Studies have shown that prealbumin can be used as a parameter of nutritional status evaluation [7] and is superior to albumin (ALB) [8]. What's more, prealbumin is also associated with postoperative recovery [9,10] and is an independent predictor of prognosis in patients with malignancies [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%